2015
DOI: 10.1080/15226514.2014.955168
|View full text |Cite
|
Sign up to set email alerts
|

Remediation and Safe Production of cd Contaminated Soil Via Multiple Cropping HyperaccumulatorSolanum nigrum L. and Low Accumulation Chinese Cabbage

Abstract: Multiple crop experiment of hyperaccumulator Solanum nigrum L. with low accumulation Chinese cabbage Fenyuanxin 3 were conducted in a cadmium (Cd) contaminated vegetable field. In the first round, the average removal rate of S. nigrum to Cd was about 10% without assisted phytoextraction reagent addition for the top soil (0-20 cm) with Cd concentration at 0.53-0.97 mg kg(-1) after its grew 90 days. As for assisted phytoextraction reagent added plots, efficiency of Cd remediation might reach at 20%. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…33 However, the study of Niu et al demonstrated that the removal rate for Cd hyperaccumulating species Solanum nigrum cultivated for 90 days was equal to an average of 11% in unassisted phytoextraction and increased twice for the process assisted by combined use of glycine, glutamic acid and cysteine. 60 In the present study the pot experiment took only 7 days. This short period of time enabled Hg to be removed at a rate of almost 20% for the process assisted by compost + NTA.…”
Section: Efficiency Of Phytoextractionmentioning
confidence: 85%
“…33 However, the study of Niu et al demonstrated that the removal rate for Cd hyperaccumulating species Solanum nigrum cultivated for 90 days was equal to an average of 11% in unassisted phytoextraction and increased twice for the process assisted by combined use of glycine, glutamic acid and cysteine. 60 In the present study the pot experiment took only 7 days. This short period of time enabled Hg to be removed at a rate of almost 20% for the process assisted by compost + NTA.…”
Section: Efficiency Of Phytoextractionmentioning
confidence: 85%
“…Two approaches were used to determine phytoextraction efficiency: (1) Cd removal efficiency from the top soil (0–20 cm) expressed in terms of the decline percentage of overall soil concentration 42 ; and (2) Cd removal efficiency from top soil in a theoretical case, calculated as % of soil metal removed by one crop = (plant metal concentration × biomass)/(soil metal concentration × soil mass in the rooting zone) × 100 43 , 44 . For comparative purposes, these two methods were adopted in this study to evaluate the phytoextraction efficiency of Cd from soil by regenerated tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Broadhurst and Chaney 2016). Co-cropping with hyperaccumulating plants may, however, provide more potential here for achieving both spoil stabilisation and phytoremediation because it would combine the biomass, surface coverage and below-ground exudates of ryegrass with the hyperaccumulating capacity of species such as yellowtuft (Alyssum murale) or black nightshade (Solanum nigrum) (Broadhurst and Chaney 2016;Niu et al 2015). Even so, phytoremediation is at best a very long term strategy, with some estimates for the time taken to achieve remediation success put at decades to hundreds or even thousands of years (Tschan et al 2009;Suman et al 2018).…”
Section: )mentioning
confidence: 99%